2009
DOI: 10.1007/s10935-009-0170-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Enrollment and Retention in a Preventive Parenting Intervention for Divorced Families

Abstract: Participation rates in parenting programs are typically low, severely limiting the public health significance of these interventions. We examined predictors of parenting program enrollment and retention in a sample of 325 divorced mothers. Predictors included intervention timing and maternal reports of child, parent, family, and sociocultural risk factors. In multivariate analyses, child maladjustment and family income-to-needs positively predicted enrollment, and higher maternal education and recruitment near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 52 publications
4
90
1
1
Order By: Relevance
“…6,7 Time constraints, child care needs, transportation issues, and work conflicts are among the challenges parents report regarding enrolling and remaining engaged in a parent education program. Recruitment rates for families of low socioeconomic status are below 31% 8 and attrition rates are high even if parents are enrolled successfully and provided with transportation and child care.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Time constraints, child care needs, transportation issues, and work conflicts are among the challenges parents report regarding enrolling and remaining engaged in a parent education program. Recruitment rates for families of low socioeconomic status are below 31% 8 and attrition rates are high even if parents are enrolled successfully and provided with transportation and child care.…”
Section: Introductionmentioning
confidence: 99%
“…Hart et al also found parents were not receptive to interventions aimed at encouraging dietary behaviour change at a family or personal level (11) . In general, engaging low-income minority parents with young children in preventive parenting interventions has been found to be challenging because of competing time commitments and priorities, unstable schedules and lack of transportation (18) .…”
mentioning
confidence: 99%
“…Another important method of parents finding out about Sure Start services is through word of mouth (TNS Social, 2009). Research indicates that enrolment on parenting courses is highest among parents who can clearly see a benefit in participating (Spoth et al, 2000), and where parents perceive that their children have behavioural problems (Seefeldt et al, 2008;Winslow et al, 2009). The content and quality of the service offered to parents affect the level of engagement (Chaffin et al, 2009).…”
Section: Engaging Families With An Early Childhood Intervention Progrmentioning
confidence: 99%
“…Catering for a complex set of conflicting interests within Sure Start catchment areas can be difficult to negotiate and may lead to some groups feeling excluded (Clarke, 2010). Obstacles to engagement include 'logistic barriers' and 'interpersonal barriers' (Winslow et al, 2009). Logistic barriers include lack of transport, problems with fitting attendance at Sure Start activities around other commitments and the financial cost of some of the Sure Start activities offered (Spoth et al, 2000;Tunstill et al, 2005;Williams and Churchill, 2006).…”
Section: Engaging Families With An Early Childhood Intervention Progrmentioning
confidence: 99%
See 1 more Smart Citation